Students’ experiences and learning objectives: Implications for future online learning - Ria Arista Asih; Lazuardy Alief (Journal of Education and Learning (EduLearn), 2022)
Positive online learning experiences during the COVID-19pandemic remain debatable in the literature where students and instructors have been enforced to shift from conventional face-to-face meetings to virtual learning. This study aims to explore English for specific purposes (ESP) students’ experiences during online learning, along with their concerns on learning attainment and personal adaptations. A qualitative case-study method was employed through interviews with students (n=19) from three private universities in Indonesia. The obtained data were analyzed through thematic analysis. Results showed that students of different departments approached ESP differently, but they similarly reported facing difficulties in reaching the learning objectives. They also experienced burnout from excessive online learning and found themselves hardly adapting to various instructors’ strategies. These findings revealed the need to revisit online ESP delivery classes in higher education. Implications for the future design of online ESP learning courses and instructor professional development are discussed.